Interactions between ABC gene polymorphisms and processing speed in predicting depression severity - Meijiang Jin; Lei Ji; Maojia Ran; Yan Bi; Hang Zhang; Yuanmei Tao; Hanmei Xu; Shoukang Zou; Hong Zhang; Tao Yu; Li Yin (BMC Psychiatry)
Abstract Background ABC family genes encode ATP-binding cassette proteins, which are involved in the transport of various substances and are associated with major depressive disorder (MDD); however, their clinical significance in MDD remains unclear. Therefore, this study aimed to investigate whether ABC family genes are associated with cognitive function, and the combined effects of genes and cognitive function on the severity of depression. Method Linear models or logistic regression models were used to investigate the associations of ABC family gene variants with clinical symptoms and cognitive function in 805 MDD patients (12–65 years old) and 1493 age-matched healthy controls (HCs). Seven single nucleotide polymorphisms (rs28401781, rs4148739, rs3747802, rs1109866, rs1109867, rs3731885, and rs3755047) of ABCB1 and ABCB6 were selected. The cognitive function was assessed by the Wisconsin Card Sorting Test (WCST), Tower of Hanoi Test (TOH), Trail Making Test (TMT), and Verbal Fluency Test (VF). Results Significant differences in gene frequency and genotype frequency were observed at the rs1109866 (X 2  = 8.22, p = 0.004; X 2  = 9.82, p = 0.007) and rs1109867 (X 2  = 7.35, p = 0.007; X 2  = 9.15, p = 0.010) between MDD patients and HCs, even after correction. While rs28401781 (t = 2.78, p = 0.006) and rs4148739 (t = 3.08, p = 0.003) were associated with the TOH test. And both rs1109866 and rs1109867 interacted with TMT results to influence depression severity in MDD patients. Conclusion The results suggest that ABC family genes influence the severity of depression through cognitive functioning, providing possible evidence for genetic markers in MDD patients.